2021
DOI: 10.51402/jle.v2i1.36
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ekstrak Propolis (Metode CMCE) Terhadap Kadar Malondialdehid (MDA) Dan Degenerasi Tubulus Renalis

Abstract: Gangguan ginjal akut (GnGA) merupakan suatu keadaan dimana proses laju filtrasi glomerulus ginjal menurun secara cepat yang menyebabkan retensi nitrogen terutama kreatinin dan blood urea nitrogen (BUN). Kondisi ini dapat dinetralkan dengan mengkonsumsi antioksidan dari luar tubuh seperti Propolis (metode CMCE). Untuk mengetahui pengaruh ekstrak propolis (metode CMCE) terhadap kadar MDA dan degenerasi tubulus renalis. Penelitian ekperimental dengan pendekatan post test only control group design. Subyek peneliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…9). Necrosis is a degeneration process that occurs after the blood supply is lost with marked cell swelling, protein denaturation and drug metabolism and body metabolism with biomolecules that make up kidney cell membranes causing necrosis (Alamsyah et al, 2021). Diameter of distal tubules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9). Necrosis is a degeneration process that occurs after the blood supply is lost with marked cell swelling, protein denaturation and drug metabolism and body metabolism with biomolecules that make up kidney cell membranes causing necrosis (Alamsyah et al, 2021). Diameter of distal tubules.…”
Section: Resultsmentioning
confidence: 99%
“…Another result was found that the addition of turmeric powder 200 mg/200gBW/head/day experienced an increase in cell size, which was significantly different compared to the treatment given a high-fat diet and the control treatment (Figure 13). This happens because cells have swelling because the injury has not eliminated water, so water is retained in the cells (Alamsyah et al, 2021). Damage in the proximal tubule can impact damage that occurs in the distal tubule because the distal tubule is the site of urine concentration (Ervina & Sukarjati, 2017).…”
Section: Resultsmentioning
confidence: 99%